A moderate fat, low-energy dry expanded diet reduces gain in body condition score when fed as part of a post neutering weight-control regimen in growing pet cats*. (30th September 2014) - Spofford, Nathaniel; Mougeot, Isabelle; Elliott, Denise A.; Addleman, Ashlee; Lefebvre, Sandra L.; Wang, Mansen; Yang, Mingyin; Feugier, Alexandre; Biourge, Vincent; Lund, Elizabeth M.
Abstract: Neutering of cats has been associated with significant weight gain in the weeks following surgery. The present study aimed to evaluate the effectiveness of a moderate fat, low-energy dry expanded diet in reducing weight gain in growing pet cats when fed as part of a weight-control regimen over the 6 months post-neutering. Cats in participating primary care veterinary hospitals were enrolled at neutering and assigned to receive one of the two dietary treatments based on the hospital of origin. Owners of cats in the treatment group were instructed to feed the trial diet at maintenance (324·7 kJ/kg BW 0·711 per d). Instructions for the control group were to feed the cat's regular diet according to the manufacturer's recommendations. Body weight and condition were evaluated by veterinarians at enrolment, 2-weeks, and 1–4 and 6 months after surgery. Body condition score (five-point scale) was compared between enrolment and each subsequent visit, controlling for enrolment age and sex. Percentage change in body weight was evaluated via multivariate mixed modelling to account for repeated measures. A total of 187 cats (eighty-seven females and 100 males) with a mean age of 5·2 (sd 0·8) months and mean weight of 2·8 (sd 0·6) kg from fifty-one hospitals completed the trial. The odds of being scored as overweight were 4·1 times as great for cats in the control v. treatment groups (95 % CI 2·1, 8·2). Percentage change in body weight differed significantly with enrolment age ( P = 0·007) and approached significance between diet groups ( P = 0·08). Cats fed the trial diet had a significantly reduced incidence of overweight in the 6 months following neutering.